Bacterial Conjugation as a Framework for the Homogenization of Tactics in Mexican Organized Crime. (3rd October 2021) - Jones, Nathan P.
Abstract: This article posits a competitive bacterial ecology as a framework for Mexican drug trafficking with a novel focus on bacterial conjugation (one type of horizontal gene transmission) to explain tactical homogenization. Individual drug traffickers consciously switch between Mexican organized crime groups sometimes three and four times, much like individual bacteria exchange their DNA in a horizontal genetic transfer that allows rapid evolution and resilience. Bacterial conjugation is a useful amplifying variable for understanding the homogenization of violence and this article probes its plausibility by providing examples of traffickers switching groups and taking tactics with them. Drawing on examples of traffickers and cells from the Arellano Felix Organization, the Sinaloa Cartel, Cartel de Jalisco Nueva Generacion, the Viagras, Zetas, and the Gulf Cartels, this article traces the genealogy of violent tactics, techniques, and procedures such as dissolving bodies in acid, asphyxiation, and infantry tactics, through individual traffickers into new groups drawn generally in the direction of more powerful, proximate, and similar trafficking groups.